Science of breeding and heredity from ancient Persia to modern Iran - Kariminejad, Mohammad H. (Medknow Publications & Media Pvt Ltd, 2012)
About 1700 years BC, the prophet Zoroaster declared equal right for women and men to choose their “own ways.” There is much evidence that ancient Persians believed in the equal contribution of women and men toward producing a child, and all its hereditary characteristics. Even more surprising are the phrases in Vandidad book, which were gathered by Mobedans in the Mad dynasty about egg extraction (gametes) from animal reproductive organs (gonads) and their storage for future conception. Centuries later, Western philosopher beliefs in regard to reproduction were contrary to Persian knowledge. The Greek philosophers believed that man's water (semen) contains all human characteristics, and the female uterus is only responsible for nurturing and development of fetus. After detection of the ovum (de Graaf 2(nd) half 17 century) Malpigy proposed the preformation theory (ovist) which means there is a miniature human inside ovum, that grows after Semen has entered the uterus and grow into a well-developed fetus. This hypothesis was later delegated to spermatozoa. These contradictory and inappropriate beliefs were subject to discussions and dispute, until C.E. Wolf demonstrated that the embryo is a product of the fertilization of ovum by spermatozoa. 800 years prior this the sage Ferdowsi “The Great Iranian Poet” explains nicely the equal participation of man and woman in the production of the fetus and transmission of characters. After the renaissance and especially in recent years, tremendous achievements have been made in unraveling biological secrets of reproduction. There was no work o n genetics in Iran until 1936, when a genetic course was added to the biology curriculum in related colleges and universities; Iranian Genetics Society was founded in 1966, initiating a steady movement in this field. Although there was an inevitable gap during the revolution and war in our country, now there is great effort by researchers to eliminate the gap and bring us into the mainstream of world science, and development in biomedical sciences in the third millennium.